Peran Pelayanan Prima terhadap Kepuasan Konsumen dan Penjualan Warteg Studi kasus di Jakarta - Jasmine, Roslinda; Adiba; Dila, Farah; Michael, Emanuel; Chaerudin, Iman (CV ODIS, 2025)
This study aims to analyze the management and development strategies of Warung Tegal (Warteg) as a form of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. A literature review of five journals indicates that price and service are the main factors influencing customer satisfaction and loyalty. Furthermore, the implementation of a marketing mix involving product innovation, competitive pricing strategies, digital promotion, and strategic location selection has been proven to enhance the competitiveness and revenue of Warteg. Excellent service strategies, such as cleanliness, friendliness, and 24-hour operational hours, serve as key differentiators amidst intense competition, although a consistent blueprint for excellent service has yet to be established.